Nonalcoholic Fatty Liver Disease Is Associated With Decreased Bone Mineral Density in Adults: A Systematic Review and Meta‐Analysis - Su, Ying‐Hao; Chien, Kuo‐Liong; Yang, Shu‐Hua; Chia, Wei‐Tso; Chen, Jen‐Hau; Chen, Yen‐Ching (Journal of bone and mineral research, 2023)
ABSTRACT This systematic review and meta‐analysis aimed to investigate the effect of nonalcoholic fatty liver disease (NAFLD) on bone mineral density (BMD) and the risk of osteoporosis and osteoporotic fracture in adults. We searched PubMed, MEDLINE, Embase, CINAHL, Web of Science, Cochrane Library, and Scopus for observational studies published from inception to January 2023 that reported adjusted effect sizes of NAFLD on BMD, osteopenia/osteoporosis, and osteoporotic fracture. The data were synthesized using multilevel and random‐effects models. A total of 19 studies were included; of these, nine (21,294 participants) evaluated the effect of NAFLD on BMD, six (133,319 participants) investigated the risk of osteoporosis, and five (227,901 participants) assessed the risk of osteoporotic fracture. This meta‐analysis showed that NAFLD was associated with decreased BMD (mean difference −0.019 g/cm2, 95% confidence interval [CI] −0.036 to −0.002, I2 = 93%) and increased risks of osteoporosis (adjusted risk ratio [RR] = 1.28, 95% CI 1.08 to 1.52, I2 = 84%) and osteoporotic fractures (adjusted RR = 1.17, 95% CI 1.00 to 1.37, I2 = 67%). Subgroup analyses revealed that NAFLD had a significantly detrimental effect on BMD in men and on the BMD of the femoral neck and total hip. Stratified analyses by ethnicity demonstrated that NAFLD was not associated with BMD, osteoporosis, or osteoporotic fracture in non‐Asian populations. The publication bias of all included studies was low; however, there was considerable heterogeneity among the studies, warranting a careful interpretation of the findings. Overall, our results suggest that NAFLD is associated with decreased BMD and an increased risk of osteoporosis or osteoporotic fractures. Male sex and the BMD of the femoral neck and total hip may be potential risk factors for decreased BMD in adults with NAFLD. Additionally, ethnic disparities were observed between Asian and non‐Asian populations regarding BMD and osteoporotic fractures. © 2023 American Society for Bone and Mineral Research (ASBMR).